Performance evaluation of lentil and chickpea genotypes in Doti district of Nepal - Hari Kumar Prasai (International Journal of Applied Biology, 2019)
Lentil and chickpea are important winter legumes of Nepal. The experiments were carried out to evaluate the agronomic performance of lentil and chickpea genotypes at research field of Regional Agricultural Research Station (RARS), Bhagetada, Doti, Nepal during winter seasons of 2012 and 2013. The 16 lentil genotypes were evaluated in both years whereas 20 and 14 genotypes of chickpea were evaluated in 2012 and 2013 respectively. The genotypes were evaluated in a randomized complete block design with three replications. The results showed that both lentil and chickpea genotypes indicated differences for their morphological traits namely plant height, flowering, maturity, pods/plant and grain yield. The combined analysis of trials over years showed that lentil genotype namely Black Masuro produced the highest grain yield (790 kg/ha) followed by LG 12 (746 kg/ha) and ILL 3111 (747 kg/ha), respectively. Similarly, chickpea genotypes namely ICCX 840508-31 produced the highest grain yield (953 kg/ha) followed by ICCX 840508-40 (911 kg/ha) and BG 372 (850 kg/ha), respectively. It is suggested that the superior genotypes derived from these experiments could be further evaluated in farmers’ fields  before making recommendation for general cultivation